Efficacy of turmeric in the treatment of oral mucositis in patients with head and neck cancer after radiotherapy or chemoradiotherapy: a systematic review and meta-analysis - Wu, Chiu-Feng; Wu, Hui-Juan; Shih, Chia-Lung; Yeh, Tzu-Pei; Ma, Wei-Fen (Frontiers in Pharmacology, 2024)
Background Oral mucositis is a major complication for head and neck cancer (HNC) patients after radiotherapy or chemotherapy. A meta-analysis was performed to assess the efficacy of turmeric in the treatment of oral mucositis in HNC patients. Methods Randomized controlled trials investigating our topic were included in the meta-analysis. The clinical outcomes considered were the severity of oral mucositis, pain level, and weight loss. Results A total of eight articles that met our inclusion criteria were included in our meta-analysis. At the 3-week follow-up visit, the turmeric group showed significantly lower grades of oral mucositis compared to the control group (p = 0.03). When compared to the placebo group, a significant difference in the degree of oral mucositis was observed at the 4-(p = 0.03) and 6-week (p < 0.00001) follow-up visits. No significant difference in pain levels was observed between the turmeric and control groups at any of the follow-up visits. However, a significant improvement in pain levels for the turmeric group when compared with the placebo group was observed only at the 6-week follow-up visit (p = 0.006). Interestingly, a significant improvement in pain levels was observed for the turmeric group at the 2-, 4-, 5-, and 6-week follow-up visits (p < 0.05) when compared to the non-placebo group. The turmeric group showed less weight loss than the control group at the final follow-up visit (p = 0.03). conclusion Our meta-analysis showed that using turmeric may be effective in improving both the severity of oral mucositis and pain levels in HNC patients who have received radiotherapy or radiochemotherapy. In addition, the turmeric group experienced less weight loss.